THE TAXONOMY OF DYNAMIC MULTI-OBJECTIVE OPTIMIZATION OF HEURISTICS ALGORITHMS IN FLOW SHOP SCHEDULING PROBLEMS: A SYSTEMATIC LITERATURE REVIEW - Singh, Harpreet; Oberoi, Jaspreet Singh; Singh, Doordarshi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This article proposes a review of flow shop scheduling at the operational level of heuristics algorithms. After defining the research scope and the concept of multi-objective optimization through scheduling, the state-of-the-art is presented. A classification based on heuristics algorithms and scheduling criteria is proposed, which details the various types of scheduling problems encountered and groups them into different categories. Results show that despite having developed in recent years, the literature on flexible scheduling remains scarce and lack a unified terminology. While research on multi-criteria scheduling has garnered a lot of attention, improving resource efficiency and reducing makespan generation is also an important step towards a greener production. Thus, research perspectives for the inclusion of time-estimates reduction concerns in scheduling are proposed based on the analysis of the literature classification.